MODEL SYSTEM DINAMICS HUBUNGAN PENDUDUK DAN KONVERSI HUTAN MENJADI PERKEBUNAN SAWIT TERHADAP EROSI TANAH DI KECAMATAN KOTO GASIB KABUPATEN SIAK - Henny Fitri Azhar; Zulkarnaini Zulkarnaini (Jurnal Ilmu Lingkungan, 2013)
The system dynamics model of causal due to the feedback between the populationand the conversion of forest into palm oil plantations with soil erosion and predicttrends in the future. This study was conducted from May to June 2012 to calculatethe rate of depreciation of forests and increase the existing palm oil plantations inKoto Gasib Siak District; describe relationships forest shrinkage rate withincreasing palm oil plantations. The results of this study indicate shrinkage hasoccurred due to conversion of forest land into oil palm plantations in the district ofKoto Gasib Siak. System dynamics model of progressive scenario (positiveinterventions) by modifying the elements of suppression of population growth, landconversion moratorium and increase oil palm plantations, rehabilitation,reforestation and revegetation on critical land and conservation land managementand soil conservation techniques proven to increase the amount of forest area andlowers the value of the actual rate of soil erosion in the district Koto Gasib Siak.